Capacitive property studies of electrochemically synthesized Co3O4 and Mn3O4 on inexpensive stainless steel current collector for supercapacitor application. Issue 10 (July 2020) - Maile, Nagesh; Shinde, S.K.; Patil, S.S.; Kim, D.-Y.; Fulari, A.V.; Lee, D.S.; Fulari, V.J.
Abstract: Co3 O4 and Mn3 O4 have been considered as pseudocapacitive nanomaterials that are suitable for use in supercapacitors (SCs) because of the apparent role of the surface capacitive current and diffusive intercalation current in their electrical charge storage mechanism. This paper presents a study of the pseudocapacitive current distribution in Co3 O4 and Mn3 O4 thin films prepared by a simple low-temperature electrodeposition method for binder-free synthesis on inexpensive stainless steel current collectors for cost-effective SC application. After preparation, the thin films were investigated by using various characterization techniques. However, in a single-electrode SC test performed with Co3 O4, both surface capacitive and diffusive intercalation currents contributed to the total current during a charging voltammogram scan, with the diffusive current dominating in the oxidation potential region. By contrast, in Mn3 O4, a relatively small capacitive current contributed to the total current in a charging voltammogram scan. The pseudocapacitive Co3 O4 and Mn3 O4 thin films exhibited maximum specific capacitances of 131 and 109 F g −1 in 2 M KOH and maximum specific discharge capacities of 14.8 and 33.0 mAh g −1, respectively, which showed their potential for use in energy storage devices.